Fertility Treatment Resulting in Live Births in Women with Asthma – Associated with Perennial Allergy? - Tidemandsen C (Journal of Asthma and Allergy, 2020)
Casper Tidemandsen,1 Anne Vejen Hansen,1 Vibeke Backer,2 Elisabeth Juul Gade,3 Zarqa Ali,4 Charlotte Suppli Ulrik1,2 1Department of Respiratory Medicine, Hvidovre Hospital, Hvidovre, Denmark; 2Institute of Clinical Medicine, University of Copenhagen, Copenhagen, Denmark; 3Department of Gynecology and Obstetrics, Rigshospitalet, Copenhagen, Denmark; 4Department of Dermatology and Wound Healing Centre, Bispebjerg Hospital, Copenhagen, DenmarkCorrespondence: Casper TidemandsenRespiratory Research Unit Hvidovre, Department of Respiratory Medicine, Hvidovre University Hospital, Kettegård Alle 30, Hvidovre DK-2650, DenmarkTel +45 50751516Email casper.tidemandsen.01@regionh.dkBackground: Asthma has been linked with prolonged time to pregnancy compared to healthy controls, also asthma has been linked to a higher need for fertility treatment. However, knowledge of the possible association between allergy and need for fertility treatment is limited. Our aim was to explore a possible difference in having had fertility treatment in women with asthma and live births in those with perennial allergy (animals, fungi and dust mites) compared to no allergy/seasonal allergy. The primary outcome of interest was fertility treatment.Patients and Methods: Women enrolled in the Management of Asthma during Pregnancy (MAP) program at Hvidovre Hospital, DK, were included in the present analysis provided they fulfilled the following criteria: 1) diagnosed with asthma and current anti-asthma therapy and 2) first visit to the respiratory outpatient clinic within the first 18 weeks of pregnancy. Participants were divided into two groups: asthma with perennial allergy (cases) and asthma with seasonal/no allergy (controls). Logistic regression analysis was applied, and findings expressed as odds ratios (OR).Results: Among women with asthma and perennial allergy (n=544 cases), 13.8% (n=75) had fertility treatment, compared to only 10.1% (n=39) among women with asthma and seasonal/no allergy (n=388, controls) (OR 1.43, 95% CI 0.95– 2.16, p=0.087). This association remained statistically insignificant after adjusting for confounders, including BMI (OR 1.19, 95% CI 0.77– 1.84, p=0.433). In women ≥ 35 years of age, 28% (n=44) and 20% (n=19), respectively, among cases and controls had fertility treatment (OR 1.60, 95% CI 0.87– 2.94, p=0.132), and likewise, statistically insignificant after adjusting for confounders (OR 1.41, 95% CI 0.74– 2.69, p< 0.293).Conclusion: In women with asthma and live births, our study revealed a trend towards an association between perennial allergy and a higher need for fertility treatment compared to seasonal/no allergy.Keywords: asthma, allergy, pregnancy, IVF, ART, fertility, atopy